PENGARUH UKURAN PERUSAHAAN TERHADAP HARGA SAHAM DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERBANKAN SYARIAH YANG TERDAFTAR DI BEI TAHUN 2017-2020 - Aulia, Rieza Nuril; Wahyuni, Ika; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2022)
The development of the economy in Indonesia is currently very fast and growing. However, this weekend the Covid 19 pandemic had a negative impact on companies such as capital structure and company size which could affect stock prices. This study aims to determine the size of the company on stock prices through capital structure as an intervening variable. The population in this study were all Islamic banking companies. The sample of this research used purposive sampling technique. Data analysis and hypothesis testing used the Structural Equation – Partial Least Square (PLS-SEM) model. The results of the direct influence hypothesis test using the Smart PLS 3.0 shows that firm size has a significant positive effect on capital structure. Firm size has stock prices. Capital structure has a significant positive effect on stock prices. The results of the direct influence hypothesis show that firm size has a positive and significant effect on stock prices through capital structure.